Application of Rapid Fluorescence Lifetime Imaging Microscopy (RapidFLIM) to Examine Dynamics of Nanoparticle Uptake in Live Cells - Aria Ahmed-Cox; Alexander M. Macmillan; Elvis Pandzic; Renee M. Whan; Maria Kavallaris (Cells, 2022)
A key challenge in nanomedicine stems from the continued need for a systematic understanding of the delivery of nanoparticles in live cells. Complexities in delivery are often influenced by the biophysical characteristics of nanoparticles, where even subtle changes to nanoparticle designs can alter cellular uptake, transport and activity. Close examination of these processes, especially with imaging, offers important insights that can aid in future nanoparticle design or translation. Rapid fluorescence lifetime imaging microscopy (RapidFLIM) is a potentially valuable technology for examining intracellular mechanisms of nanoparticle delivery by directly correlating visual data with changes in the biological environment. To date, applications for this technology in nanoparticle research have not been explored. A PicoQuant RapidFLIM system was used together with commercial silica nanoparticles to follow particle uptake in glioblastoma cells. Importantly, RapidFLIM imaging showed significantly improved image acquisition speeds over traditional FLIM, which enabled the tracking of nanoparticle uptake into subcellular compartments. We determined mean lifetime changes and used this to delineate significant changes in nanoparticle lifetimes (>0.39 ns), which showed clustering of these tracks proximal to both extracellular and nuclear membrane boundaries. These findings demonstrate the ability of RapidFLIM to track, localize and quantify changes in single nanoparticle fluorescence lifetimes and highlight RapidFLIM as a valuable tool for multiparameter visualization and analysis of nanoparticle molecular dynamics in live cells.